Gamification Intervention on Student Academic Performance in Private Secondary School - Adeoye, Moses Adeleke (Universitas Pendidikan Ganesha, 2024)
Gamification interventions incorporate game elements into educational activities to enhance student engagement and motivation. The study aims to analyze in-depth effects of gamification on student academic performance in a particular private secondary school in Nigeria. The research design adopted for this study is a case study design. The populations of the study were all junior secondary school students. Likert-scale rating open-ended questions are used to gather quantitative data. The research collects quantitative data on the perceptions of students, teachers and administrators regarding the gamification intervention's effectiveness, feasibility and sustainability. The data were analyzed using descriptive statistics and inferential statistics, such as correlation analysis and t-tests. The study reveals that students generally support the integration of gamification in their learning environments. They believe it makes learning more enjoyable, helps them understand difficult concepts better, and enhances their learning experience. A significant proportion of students strongly agree or strongly agree that gamification has improved their academic performance, increased their confidence in understanding subjects, and improved their overall learning outcomes.